DEVELOPMENT OF FLEXIBLE ELECTRODE FROM FABRIC FOR APPLICATIONS TO MEASUREMENT OF ELECTRICITY BIOPOTENTIAL WITH EMG - Nurul Zahrani, Raisa
Electromyography (EMG) is a technique for measuring the electrical biopotential generated from muscle cell activity. The electrodes used for EMG measurements are generally dry electrodes and wet electrodes. Both types of electrodes have weaknesses such as poor contact of the electrode with the skin, difficult measurements to be made on the curves of the body, and causing discomfort to the patient when the measurement takes place. This is due to the stiff nature of the dry electrode and the use of gel on the wet electrode which can provide good measurement sensitivity for a while and has the potential to cause skin irritation. In this study, flexible cloth electrodes were made with the hope of providing a good EMG measurement signal as well as providing comfort and convenience in the EMG measurement process. The electrodes are fabricated from cotton cloth which has been coated with polyaniline and MWCNT. Polyaniline was chosen because it has a high electrical conductivity in the emerald form, and has good stability and flexibility. The fabrication process was carried out using the COP method from aniline monomer mixed with ammonium persulfate initiator in an acidic medium. The performance of cloth-based flexible electrodes was compared to that of commercial Ag/AgCl gel electrodes. The fabric electrodes fabricated in this study have been characterized as having an electrical conductivity of 75.192 S/m and a measured EMG signal SNR of 23.855 dB.